Chemotherapy Used to Halt Lower GI Bleeding in a Rare Case of Metastatic Choriocarcinoma to the GI Tract - Ralph Kamel; Talal Seoud; Teniola Oluwadamilola; Michael Karass; Emily Grossniklaus; Gabriela Oprea-Ilies; Daniel A. Goldstein; Sanjay Jain (Case Reports in Oncological Medicine)
Choriocarcinoma, a nonseminomatous germ cell tumor, is a rare type of testicular malignancy that tends to occur in young males. It is, however, exceedingly rare for choriocarcinoma to involve the GI tract. In this article, we present a rare case of a 31-year-old male, diagnosed with choriocarcinoma of the left testes, along with several metastases to distant sites. The patient presented with headaches and severe lower GI bleeding due to metastases to the GI tract, which was eventually controlled with systemic chemotherapy, while requiring several units of packed RBCs during his admission to the hospital. An extensive literature review found very few cases of the occurrence of GI bleeding as a consequence of choriocarcinoma due to metastases to the GI tract.